A Review Of Midkine As Biomarker Protein For Diagnostic Several Dieases - M. Jawad, Murtadha; H. Hussein, Asmaa (Medical Science Journal for Advance Research, 2022)
Background: This review deals with a collection of information about a protein marker that is very important and alternates presence in many cases of normal and pathological growth, as it can be observed in high concentrations in the stages of fetal development and can be expressed significantly in many cases and disorders and midkine is considered a diagnostic marker for them as in types of cancers. It has a protein structure of 121 amino acids and its expression is located on the eleventh chromosome and has several functions, especially its expression in nervous tissues during the mid-gestation. Conclusion: Midkine plays an important role in the inflammatory process in terms of its importance in the infiltration of immune cells into the peripheral organs and targeting midkine may be a viable new therapeutic option for chronic infections, especially infections of the kidneys, joints, nervous system and colon.